1997
DOI: 10.1002/jhrc.1240201103
|View full text |Cite
|
Sign up to set email alerts
|

Determination of acylglycerols in vegetable oil methyl esters by on‐line normal phase LC‐GC

Abstract: An on-line LC-GC method for the analysis of mono-, di-, and triacylglycerols in vegetable oil methyl esters has been developed. The concentrations of these components have turned out to be key parameters for the quality of diesel fuel substitutes. Separation of all classes of acylglycerols from the fatty acid methyl ester matrix is achieved by LC after acetylation of the hydroxyl groups. The acylglycerol fraction is transferred on-line to GC, using the looptype interface and concurrent eluent evaporation. Quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 19 publications
(1 reference statement)
0
16
0
Order By: Relevance
“…Biodiesel was also analyzed by GC for minor components such as sterols (14,15). Preseparation of biodiesel and its contaminants by high-performance liquid chromatography (HPLC) prior to GC was reported (16). However, other methods have been utilized in the analysis of biodiesel, including HPLC with density detection (17) or pulsed amperometric detection for determining glycerol (18), and viscosity (19).…”
mentioning
confidence: 99%
“…Biodiesel was also analyzed by GC for minor components such as sterols (14,15). Preseparation of biodiesel and its contaminants by high-performance liquid chromatography (HPLC) prior to GC was reported (16). However, other methods have been utilized in the analysis of biodiesel, including HPLC with density detection (17) or pulsed amperometric detection for determining glycerol (18), and viscosity (19).…”
mentioning
confidence: 99%
“…Many analytical methods have been used for the study of biodiesel transesterification (1). Among these, GC and LC-GC have been most widely used because of their accuracy in quantifying not only TG and FAME but also the intermediate reaction products, DG and MG (2,3). However, GC requires sample derivatization, which is time-consuming.…”
mentioning
confidence: 99%
“…Several separation and analytical techniques such as gas chromatography (GC), thin-layer chromatography, highperformance liquid chromatography (HPLC), and infrared techniques [3,4,10] have been simplified, automated, and used to identify and measure fuel quality indices. According to Plattner [11] and other workers [12,13], the commonly used GC method for BD quantitation is not a convenient or direct analytical method for the detection and quantitation of the contaminants (triacylglycerols (TAG), diacylgylcerol (DAG), monoacylglycerol (MAG), free fatty acid (FFA), glycerol, and unreacted alcohol) in the products. They further indicated that the commonly used GC methods require carefully controlled sample derivatization (trimethylsilylation or acetylation) prior to the GC analysis [3,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…According to Plattner [11] and other workers [12,13], the commonly used GC method for BD quantitation is not a convenient or direct analytical method for the detection and quantitation of the contaminants (triacylglycerols (TAG), diacylgylcerol (DAG), monoacylglycerol (MAG), free fatty acid (FFA), glycerol, and unreacted alcohol) in the products. They further indicated that the commonly used GC methods require carefully controlled sample derivatization (trimethylsilylation or acetylation) prior to the GC analysis [3,13,14]. In addition, an inert, short capillary column with stable and high column temperature (≥350°C) as well as elaborate pretreatment steps to separate the glycerol from the BD is usually required [11,15].…”
Section: Introductionmentioning
confidence: 99%